Agricultural development technology transfer : some problems and issues - Mohd Yassin, Sulaiman (1982)
The transfer technology within agricultural development in Malaysia is examined. A general survey is made on the major areas of technology transfer and problems faced in its implementation from the perspective of the user. Emphasis is made on the problems and issues that result directly or indirectly from the technology transfer process with respect to poverty redressal, technology appropriateness, farm production functions and behaviour of users and development agents. Past lessons learnt in Malaysia or within the region are also posited as an additional basis to recommend possible steps to facilitate the technology transfer process.